Prioritas Lokasi Penyediaan Lahan Dalam Upaya Pemenuhan Ruang Terbuka Hijau Publik Di Kawasan Perkotaan Bulukumba - Amri, Ulil; Jufriadi, Jufriadi; Yahya, Ilham (Journal of Urban Planning Studies, 2023)
ABSTRACT Ulil Amri Khalis, 2022 "Priority of Land Provision Locations in Efforts to Fulfill Public Green Open Spaces in the Urban Area of Bulukumba". Supervised by Jufriadi and Ilham Yahya Green Open Space (RTH) so far has an important role in an urban area, especially Public Green Open Space (RTH) in realizing a sustainable urban area. The purpose of this research is to find out potential land so that it can be prioritized in an effort to fulfill Public Green Open Spaces (RTH) and find out the direction and level of need for Public Green Open Spaces (RTH) in Urban Areas of Bulukumba Regency. This study uses the method of analysis of proportions, potential and SWOT analysis. Based on the results of field surveys and analysis, the potential for Green Open Spaces in each urban area still has great potential for development but is constrained by the provision of land whose land ownership status belongs to the community and based on the results of a swot analysis for direction and level of need for Public Green Open Spaces (RTH) in the Urban Area of Bulukumba can be done in various ways, namely: Capture and take advantage of existing opportunities by maximizing strengths to minimize weaknesses and threats. Keywords: Public, Green Open Space, Land, Priority